Auditor independence, auditor specialisation and earnings management: further evidence from Singapore - Rusmin, Rusmin; Van Der Zahn, J-L.; Tower, Greg; Brown, Alistair (Inderscience Enterprises, 2006)
This study uses data from 298 Singapore publicly listed firms to examine the association between earnings management and two audit value attributes: auditor independence and auditor specialisation. We find firms engaging a specialist auditor had significantly lower levels of abnormal accruals than those using non-specialists. This supports the view industry specialisation better enables an auditor to constrain a client's earnings management. Our findings indicate the lack of a universal association between audit value attributes and earnings management. Results imply recent action of Singapore policymakers to strengthen rules governing audit independence as related to non-audit services may have been premature.